MISKONSEPSI OPERASI BILANGAN BULAT DENGAN METODE CERTAINTY OF RESPONSE INDEX TERMODIFIKASI DI KELAS VII - Distari, Distari; Yani T, Ahmad; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThis study aims to describe the variety of misconceptions in solving addition and substraction of integers with the method of CRI (Certainty of Response Index) modified in the seventh grade of SMP Kapuas Pontianak. This study uses descriptive method with case study as its methodology. The subject of this study is all of the students of seventh grade of SMP Kapuas Pontianak with misconceptions experienced by students complete on the addition and substruction of integers as the object of this study. This study shows that the variety of misconceptions experienced by students on the addition of integers are systematic misconception, random misconception, and the misconceptions caused by carelessness. While the variety of misconceptions experienced by students on the substruction of integers are systematic misconception, random misconception, misconceptions caused by carelessnessÂ and the misconception that does not belong to any of the above types. Overall it can be concluded that on the addition of integers, students only experience 3 of 4 misconceptions that exist. While on the substraction, students experienced all the existing misconceptions.Â Keywords: Misconceptions, Operations of Integers